Cute Cookies : 50 Simply Scrumptious Recipes - Edited by Cathie, Kyle (Great Britain Kyle Books, 2011)
Offers recipes for biscuits and cookies and some creative reinventions of old classics. Packed with baking tips and modern photography, this book provides ideas for sweet and savoury, children's and adult's, seasonal and special occasion biscuits.
Include Colour Illustrations and Index
Keywords: Cookies